Transcultural Nursing Approach in Designing the Multisensory Room for Older Adults: Sensory Utilities and Activity Exploration - Umi Hani; Rita Hadi Widyastuti; Fery Agusman Motuho Mendrofa (GLOBAL HEALTH SCIENCE GROUP, 2024)
Multisensory space applies sensory stimulation that helps train cognitive and motor functions through elements that stimulate the senses in the elderly. This concept is identified for people with moderate to severe cognitive decline and neurodegenerative pathologies. Aim: This study aimed to identify sensory utilities and activities in designing a multisensory space with a transcultural nursing approach. Methods: Researchers collected data qualitatively using the Focus Group Discussion (FGD) technique to explore elements related to the function of the multisensory space. The FGD also identified transcultural nursing aspects that could be applied to the room concept. The FGD involved five participants selected according to the research objectives to explore the needs and activities of multisensory stimulation for the elderly. The FGD was conducted for two hours. Participants were the health service officer, geriatric nurses, one Alzheimer's dementia activist, one architect, and one cultural figures. The results of the FGD were analyzed using the Colaizzi method approach by transcribing data from the FGD results, reading the FGD transcripts several times, and analyzing themes using Atlas.ti. Transcripts and meaningful statements were returned to participants to form categories, subthemes, and themes. Results: The themes analyzed were related to elements in the multisensory room which included both equipment and activities that supported sensory stimulation. Discussion: The identification of spatial elements and research partners in the development of multisensory space design supports the fulfillment of the needs of applicable and innovative elderly health services, especially in applying the concept of transcultural nursing for multisensory rooms for the elderly Conclusion: Cultural considerations play a significant role in the effectiveness of sensory elements, as sensory experiences that resonate with an individual’s cultural background can evoke positive emotions and memories.